The rules to break : a personal code for living your life, your way - Templar, Richard, 1950-2006 (Pearson Education Limited, 2023)
POPULAR CULTURE. From a very young age you've been inundated with other people's rules - parents, teachers, friends - helpful principles, friendly advice, and little pointers to help you get on in life. So, how do you free yourself from these false or unhelpful beliefs that have somehow become ingrained in the deepest recesses of your mind? In this brand new book, international bestselling author Richard Templar exposes the most common imposter rules, and offers a refreshing perspective and a new way of thinking. Above all, Templar helps you master the ability to truly think for yourself, and follow a path that you've chosen, rather than blindly following someone else's.